Synthesis of Tetracyclic Benzazole–Condensed Quinazolinones through Triphenylbismuth Dichloride Assisted Cyclodesulfurization - Koyanagi, Arisu; Murata, Yuki; Takeshita, Chisaki; Kato, Yuki; Matsumura, Mio; Yasuike, Shuji (Synthesis, 2024)
Benzazole-condensed quinazolinones, such as benzo[4,5]imidazo[2,1-b]- and benzo[4,5]oxazolo[2,3-b]quinazolinones are of a great interest because of their potential applications as biologically active substances. Herein, we report that the treatment of various o-phenylenediamines with methyl 2-isothiocyanatobenzoate afforded thioxoquinazolinones, which were reacted in situ with triphenylbismuth dichloride in the presence of K2CO3 to give the desired benzimidazoquinazolinones in good to excellent yields under mild conditions. Triphenylbismuth dichloride promoted the conversion of thioxoquinazolinone to tetracyclic products as an efficient cyclodesulfurization reagent. All the steps in this tandem reaction were performed at room temperature. The present reaction system can also be applied to benzoxazoloquinazolinone synthesis by using 2-aminophenols as the starting material.
Keywords: benzimidazoquinazolinone; triphenylbismuth dichloride; cyclodesulfurization; one-pot tandem reaction; aminophenol